GRAPHIC MODEL OF PROFESSIONAL ACTIVITY. GRAPHICAL ANALYSIS METHOD - Zaritskyi, Oleh; Pavlenko, Petr (Proceedings of National Aviation University (archive), 2019)
Currently, various scientific schools use several methods for analyzing the work, which, as a rule, are based on one of the four methods developed at the beginning of the twentieth century. There are also no scientific papers that would consider professional activity from the point of view of systems analysis, as a complex open socio-technical system of interrelated operations (tasks). In this regard, the issues of developing a graphical model of professional activity and assessing the characteristics of its elements is a relevant scientific task. Analysis of recent research and publications, problem statement. The article discusses the main disadvantages inherent in existing methods and systems. The solution of these shortcomings is possible by resolving the contradiction, which is the need to simultaneously ensure the universality of the model on the one hand and its adequacy on the other. The solution of this contradiction is possible through the development of completely new approaches in the provision of professional activities, including in the form of a graphical model. The purpose and objectives of the study. The purpose of the study is to obtain the necessary and sufficient for the analysis of professional activity a number of characteristics that describe its components - operations (tasks). The main task to achieve this goal is to build a graphical model and study the main characteristics of its nodes. Materials and research methods. To solve the problem of the study were used: the method of expert evaluation (in the process of evaluating the characteristics of the work); parametric and non-parametric methods of mathematical statistics; graph theory for constructing a graphical model and its research. Research results. A method of graphical analysis of professional activity has been developed, which provides for the analysis of data on operations and relations between them, the automatic formation of adjacency matrices, incidents, and the calculation of the coefficients of operations and activities in general. The discussion of the results. All the considered coefficients exhaustively characterize operations in terms of their importance and place in their professional activities. The developed method of graphical analysis of professional activity is aimed at solving the problem of evaluating the characteristics of each operation as a structural element of the “professional activity” system.